Health literacy amongst tuberculosis patients in a general hospital in North Central Nigeria. (2013)
Background: Healthy literacy has been shown to improve health care access and adherence to Tuberculosis (TB) treatment. Still it remains largely unstudied in many high risks, underserved and low literacy African populations. This study aims to bridge the existing knowledge gap by assessing health literacy among patients with TB in a rural town in Northern Nigeria. Methodology: A cross sectional study was conducted among patients who attended the TB clinic of a secondary health care facility in Babura, Jigawa State, Nigeria between Oct 2008 and March 2009. All patients who visited the TB clinic during this period were interviewed. Result: Many (71.6%) reported having been educated about TB by a health worker, mostly on predisposing factors 43.2%, general facts (31.1%) and disease process (21.6%) but less on patient's role in disease management (1.4%). Functional health literacy was high; mean score was 7.9±0.3 out of 10. Knowledge about the disease process, diagnostic requirements and treatment regimen were the highest. However 97.3% felt drugs were no longer necessary once symptoms abated. Patient involvement in treatment decisions was also suboptimal as only 52.7% reported making a joint decision about drug “pick up” options with their physicians. Conclusion: Very high functional literacy score seemed to have been achieved among these rural low literacy TB patients even without a structured health literacy program. However patient participation in treatment seems to be underemphasized and was thus suboptimal. An important gap in patient education regarding continued TB treatment was identified and should be targeted for intervention.